2016
DOI: 10.21037/tcr.2016.10.55
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression and expression quantitative trait loci analyses of the angiogenesis gene-gene interaction network in prostate cancer

Abstract: Background Prostate cancer (PCa) shows a substantial clinical heterogeneity. The existing risk classification for PCa prognosis based on clinical factors is not sufficient. Although some biomarkers for PCa aggressiveness have been identified, their underlying functional mechanisms are still unclear. We previously reported a gene-gene interaction network associated with PCa aggressiveness based on single nucleotide polymorphism (SNP)-SNP interactions in the angiogenesis pathway. The goal of this study is to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…These three genes (CASC11, MYC, and PVT1) are physically close to each other, and their interactions associated with prostate cancer risk remain unknown, especially for AA men. It is suggested that SNP-SNP interactions have a large impact on revealing the mechanism of complex diseases (29)(30)(31)(32)(33)(34). Individual SNP effects are well known to have low prediction power despite of the fact that large numbers of GWAS SNPs have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…These three genes (CASC11, MYC, and PVT1) are physically close to each other, and their interactions associated with prostate cancer risk remain unknown, especially for AA men. It is suggested that SNP-SNP interactions have a large impact on revealing the mechanism of complex diseases (29)(30)(31)(32)(33)(34). Individual SNP effects are well known to have low prediction power despite of the fact that large numbers of GWAS SNPs have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…ROBO1 acts like a natural inhibitor of metastasis; therefore, ROBO1 is considered as a potential cancer therapeutic target [ 58 ]. We previously reported several SNP–SNP interactions between R0BO1 and MMP16 associated PCa aggressiveness, and the biological function of the ROBO1–MMP16 interactions was supported by gene expression results [ 21 , 59 ]. ROBO1 is one gene enriched in the axon guidance pathway, significantly associated with alcoholism and alcohol addiction [ 60 ].…”
Section: Discussionmentioning
confidence: 84%
“…A single study reported that MT2-MMP is downregulated in PrCa [ 38 ], but in contrast, MT3-MMP expression was increased and correlated with enhanced aggressiveness/metastatic potential [ 38 , 166 , 167 , 172 ]. Likewise, MT6-MMP expression was generally observed to be increased in PrCa [ 155 , 165 ], including one study that indicated a correlation with the PrCa grade [ 115 ].…”
Section: Resultsmentioning
confidence: 99%